Death by peppermint cappuccino - Erickson, Alex (Erickson, Alex. Bookstore café mystery., 2023)
"Christmas has come to Pine Hills, and Krissy's blooming relationship with Officer Paul Dalton has her in an especially festive mood. The café's new seasonal signature drink is a hit too. But not everyone shares the same holiday spirit. There are some loud complaints about businesses profiting off the season and losing focus on what Christmas is really about. And as if on cue, a shop owner who'd been price-gouging his customers is found dead after receiving a mysterious gift... Krissy doesn't want to let the troubling events put a damper on the holiday, especially with her father and his girlfriend in town. But when other shop owners are targeted she has no choice. She needs to wrap up this case quickly before one of her friends--or even Krissy herself--ends up on a Grinchy killer's deadly gift list..."--